Chemical Modification and Performance Evaluation of an Agro‐Waste for Column Mode Removal of Textile Dyes. Issue 10 (23rd July 2018) - Samchetshabam, Gita; Shukla, Satya Prakash; Matolia, Jyoti; Prakash, Chandra; Bharti, Vidyashree; Singh, Arvind Rajdeo
Abstract: The performance of a newly designed column bed device packed with chemically modified agro‐waste (sugarcane bagasse) is evaluated for efficient removal of two textile dyes, Optilan yellow and Lanasyn brown and textile industry dye effluent. The parameters used for performance evaluation are removal efficiency ( R %), adsorption capacity ( q ), and breakthrough ( C e / C 0 ). The column exhibits >90% removal of both the dyes and >80% removal of textile industry dye effluent. The experimental data are fitted to three models, viz., Thomas, Adams–Bohart, and Yoon–Nelson for understanding the kinetic behavior of adsorption. The results reveal that the Yoon–Nelson model is the best‐fitted model for both the dyes with R 2 values 0.995 and 0.905 for Optilan yellow and Lanasyn brown, respectively. However, Thomas and Yoon–Nelson fit the best for textile industry effluent. Overall, this investigation provides baseline information about the column mode removal of textile dyes using the agro‐waste material as an adsorbent. The Fourier transform infrared spectroscopy spectra show the characteristic vibrational mode of CH stretching of hydroxyl group around 2800–3000 cm −1 . The change in the vibrational pattern is evident after alginic acid treatment, indicating delignification of the bagasse after treatment. Abstract : Performance of a newly designed column bed device packed with chemically modified sugarcane bagasse is evaluated for efficient removal of two textile dyes, Optilan yellow and Lanasyn brown, and textile industry dye effluents. The column exhibited > 90 % removal of both the dyes and > 80% removal of textile industry dye effluent.